2018
DOI: 10.1371/journal.pone.0202954
|View full text |Cite
|
Sign up to set email alerts
|

Extending the functional characteristics of naturally occurring autoantibodies against β-Amyloid, Prion Protein and α-Synuclein

Abstract: BackgroundAbnormal aggregation of proteins induces neuronal cell loss in neurodegenerative disorders such as Alzheimer’s Disease, Creutzfeldt-Jakob Disease and Parkinson’s Disease. Specific stimuli initialize conformational changes in physiological proteins, causing intra- or extracellular protein aggregation. We and other groups have identified naturally occurring autoantibodies (nAbs) as part of the human antibody pool that are able to prevent peptide fibrillation. These nAbs show a rescue effect following e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 44 publications
(50 reference statements)
0
9
0
Order By: Relevance
“…We speculate that the increase in anti-αSyn nAb responses is triggered by a higher load of peripheral αSyn in these patients, however, as the high-affinity antibody pool is reduced, this increased IgG1 production may be characterized by a lower affinity profile, resulting in diminished capacity for immune clearance leading to αSyn aggregation. In support of this, it was recently shown that anti-αSyn nAbs present in healthy individuals not only recognize different αSyn structures [ 32 ], but also inhibit the aggregation of αSyn by altering fibril formation in cell culture [ 33 ]. Further, anti-αSyn nAbs isolated from IVIg has shown rescuing effects in both low- and high-dose paradigms in the A53T transgenic PD mice model [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that the increase in anti-αSyn nAb responses is triggered by a higher load of peripheral αSyn in these patients, however, as the high-affinity antibody pool is reduced, this increased IgG1 production may be characterized by a lower affinity profile, resulting in diminished capacity for immune clearance leading to αSyn aggregation. In support of this, it was recently shown that anti-αSyn nAbs present in healthy individuals not only recognize different αSyn structures [ 32 ], but also inhibit the aggregation of αSyn by altering fibril formation in cell culture [ 33 ]. Further, anti-αSyn nAbs isolated from IVIg has shown rescuing effects in both low- and high-dose paradigms in the A53T transgenic PD mice model [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, nAbs-αSyn are already present in early childhood with levels comparable to healthy adult controls [45]. The binding of nAbs to αSyn monomers, oligomers, and fibrils could be confirmed using dot blot, surface plasmon resonance (SPR) and enzyme-linked immunosorbent assay (ELISA) [26,46]. nAbs-αSyn purified from commercial intravenous immunoglobulins (IVIG) using αSyn oligomers inhibit aggregation of αSyn as reported by thioflavin T (ThT) fluorescence [26].…”
Section: Introductionmentioning
confidence: 92%
“…nAbs-αSyn were isolated from IVIG as previously described [46]. Briefly, we used purified intravenous immunoglobulin G (IgG) (Gamunex 10%, 100 mg/mL, Grifols, Barclona, Spain).…”
Section: Gravity Flow Affinity Purification Of Nabsmentioning
confidence: 99%
“…This changed the concentration of other IgG in the samples, which might influence the binding characteristics of nAbs-α-Syn in the SPR experiments. Importantly, we identified a unique α-Syn bond using nAbs-α-Syn, and no further IgG in these samples seemed to detect the epitope [ 17 ].…”
Section: Limitation Of the Studymentioning
confidence: 99%